1981
DOI: 10.1093/oxfordjournals.aje.a113207
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiologic Study of Epithelial Carcinoma of the Ovary

Abstract: A case-control study to identify risk factors for epithelial ovarian cancer was undertaken among women in the age group 45-74 years who had been admitted to seven hospitals in Connecticut between July, 1977, and March, 1979. Characteristics that were found to increase the risk of epithelial ovarian cancer included being white, never having been pregnant, having a late age at menopause, having a family history of cancer of the ovary or endometrium, and having a long estimated number of years of ovulation. Prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
89
1
7

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(107 citation statements)
references
References 12 publications
9
89
1
7
Order By: Relevance
“…In conclusion, the findings of the present study add further support to the evidence, emerging mainly from American data (McGowan et al, 1979;Annegers et al, 1979;Hildreth et al, 1981;Weiss et al, 1981;Willett et al, 1981;Rosenberg et al, 1982;Cramer et al, 1982;Casagrande et al, 1983; Centers for Disease Control Cancer and Steroid Hormone Study, 1983), of a reduction of -40% in the risk of epithelial ovarian cancer among women who had used oral contraceptives. This result is statistically significant, even with a considerably lower proportion of ever users (15% in the comparison group of this series versus 30-60% in American series of comparable age, Rosenberg et al, 1982;Centers for Disease Control Cancer and Steroid Hormone Study, 1983), and with a shorter average duration of use.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In conclusion, the findings of the present study add further support to the evidence, emerging mainly from American data (McGowan et al, 1979;Annegers et al, 1979;Hildreth et al, 1981;Weiss et al, 1981;Willett et al, 1981;Rosenberg et al, 1982;Cramer et al, 1982;Casagrande et al, 1983; Centers for Disease Control Cancer and Steroid Hormone Study, 1983), of a reduction of -40% in the risk of epithelial ovarian cancer among women who had used oral contraceptives. This result is statistically significant, even with a considerably lower proportion of ever users (15% in the comparison group of this series versus 30-60% in American series of comparable age, Rosenberg et al, 1982;Centers for Disease Control Cancer and Steroid Hormone Study, 1983), and with a shorter average duration of use.…”
Section: Discussionsupporting
confidence: 88%
“…Evidence from several case-control studies conducted mainly in North America (McGowan et al, 1979;Annegers et al, 1979;Hildreth et al, 1981;Weiss et al, 1981;Willett et al, 1981;Rosenberg et al, 1982;Cramer et al, 1982;Casagrande et al, 1983; Centers for Disease Control Cancer and Steroid Hormone Study, 1983; see also Newhouse et al, 1977) suggests that the use of cQmbined oral contraceptives (OCs) reduces the risk of epthelial ovarian cancer. General lifestyle and reproductive characteristics, however, are notoriously different in Italy.…”
mentioning
confidence: 99%
“…The raised risk for women with a first pregnancy after 35 years persisted (RR = 3.9, 95% CI 1.1-14.2). Results from other studies regarding the risk for women having a first child at relatively older ages are inconclusive, some finding no association (Newhouse et al, 1977;Casagrande et al, 1979;Cramer et al, 1983;Lesher et al, 1985), others an increased risk (Joly et al, 1974;McGowan et al, 1979;Hildreth et al, 1981;Franceschi et al, 1982). Only Franceschi et al (1982) found the increased risk to be statistically significant and independent of parity.…”
Section: Discussionmentioning
confidence: 97%
“…This incidence curve suggests that the menopause protects women against breast cancer, and this has been established directly by epidemiological studies (Kelsey, 1979;Moore et al, 1983). The age-incidence curves for ovarian and endometrial cancer show a similar pattern; both show a distinct change in slope around age 50 and early menopause has been shown to protect against both of these cancers (Elwood et al, 1977;Hildreth et al, 1981;Pike, 1987). Early artificial menopause (bilateral ovariectomy) has been shown to provide at least equally effective protection against breast cancer and against endometrial cancer (Elwood et al, 1977;Kelsey, 1979).…”
mentioning
confidence: 85%
“…Cancer of the ovary In addition to early menopause, the other two risk factors that have been consistently found in epidemiological studies of ovarian cancer are parity and use of COCs (Hildreth et al, 1981;Henderson et al, 1983;Pike, 1987 very successfully modelled mathematically by assuming that the age-incidence curve has the shallow post-menopausal slope when a woman is not ovulating (Pike, 1987 …”
mentioning
confidence: 99%